Penentuan Efek Serbuk Kunyit (Curcuma Domestica Val.) Dalam Sediaan Salep Sederhana Untuk Mengobati Luka Bakar Pada Kulit Marmut Betina - Ainun Naim; M. Ridho Fajri (Journal Pharma Saintika, 2022)
Research has been carried out to test and determine the effects of turmeric (Curcuma Domestica Val.) powder in simple ointment preparations to treat burns on the skin of female guinea pigs, based on the literature, turmeric contains curcumin compounds, and the benefits of turmeric as an antiseptic in healing burns, from Statistical tests that have been carried out show that the data are normally distributed using the Liliford test, the data has a homogeneous variance using the Barlet test. Meanwhile, in the anava test, Fcount was 0.537 £ Ftable 4.60 with a= 0.01 indicating that there was no significant difference between the test substance groups at 5% concentration, 10% concentration and 20% concentration